Knowledge Level of Adolescent Women about Prevention of Cervic Cancer in Mayjend Sutoyo Medan Foundation High School High School, Medan In 2019 - Henni Safrida Sitompul (Science Midwifery, 2021)
Cervical cancer or cervical cancer is the most common cancer among women. Cervical cancer attacks the female reproductive organs and uterus. Every year thousands of women die from cervical cancer. Poor living habits can also cause outbreaks of cervical cancer, such as smoking, lack of nutrition, long-term use of oral contraceptives, sexual activity that is often among adolescents. The level of knowledge of young women about cervical cancer prevention in the Mayjend Sutoyo College Foundation Senior High School Medan. World Health Organization (WHO) states, currently cervical cancer is ranked among the various types of cancer that causes death in women in the world. Cervical cancer can be prevented by doing primary prevention and secondary prevention. This type of research is a descriptive study conducted. The population in this study were female students at the Major General Sutoyo College Foundation in Medan. A sample of 39 people were taken in total sampling. Data obtained using a questionnaire. The conclusion of the study is the level of knowledge of young women in the Mayjend Sutoyo Medan Foundation High School in the prevention of cervical cancer is still in the sufficient category.